2023
DOI: 10.30935/ojcmt/13572
|View full text |Cite
|
Sign up to set email alerts
|

Using ChatGPT in academic writing is (not) a form of plagiarism: What does the literature say?

Abstract: This study aims to review the existing literature on using ChatGPT in academic writing and its implications regarding plagiarism. Various databases, including Scopus, Google Scholar, ScienceDirect, and ProQuest, were searched using specific keywords related to ChatGPT in academia, academic research, higher education, academic publishing, and ethical challenges. The review provides an overview of studies investigating the use of ChatGPT in academic writing and its potential association with plagiarism. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 39 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…To develop the scale, it was crucial to determine the loading values of the scale items on their respective dimensions, as illustrated in Figure 3 . The loading factors of the items needed to meet the criterion that items with loading factors less than 0.40 should not be adopted [ 50 ]. The results indicate that all items have loading factors greater than 0.40 within their respective dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…To develop the scale, it was crucial to determine the loading values of the scale items on their respective dimensions, as illustrated in Figure 3 . The loading factors of the items needed to meet the criterion that items with loading factors less than 0.40 should not be adopted [ 50 ]. The results indicate that all items have loading factors greater than 0.40 within their respective dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…Research consistently highlights the importance of inclusive design and equitable access initiatives to mitigate disparities and ensure ChatGPT benefits all students. In the writing process, ChatGPT facilitates researchers globally by expediting concept exploration, draft generation, and rapid information gathering (Jarrah et al, 2023;Macdonald et al, 2023;Vijayakumar, 2023). In the South African context, the implementation of ChatGPT raises unique challenges due to disparities in access and a diverse linguistic context (Naidu & Sevnarayan, 2023).…”
Section: Equity and Accessibility Implications Of Chatgpt Implementationmentioning
confidence: 99%
“…Furthermore, the ethical hazards connected with AI-based technology should also be evaluated in terms of digital literacy (Dempere et al, 2023). Many studies indicated that it was decisive to adopt acceptable procedures in order to maintain academic integrity and make certain that the use was ethical (Jarrah et al, 2023). Therefore, it was of significance for learners to leverage the benefits of ChatGPT while becoming responsible users and understanding their duties in educational settings (Kohnke et al, 2023).…”
Section: Rq4:could Digital Literacy Positively Influence Learners' Ou...mentioning
confidence: 99%